Domestic workload and its relationship with the academic performance of female architecture students at a private university, Piura, Peru, 2025 - Escobar Carreño, Abner Josue; More Ayala, Samantha Aymee (LACCEI, 2025)
The main objective of this research was to determine the relationship between household load and the academic performance of female architecture students at a private university in Piura, Peru. The research methodology was basic, with no alteration of any variables (non-experimental), simple correlational, and cross-sectional. The population consisted of 416 female architecture students, and the sample consisted of 200. A significant relationship (0.000) was found. This correlation is highly negative. This implies that the greater the household load, the lower the academic performance of female architecture students.